2009
DOI: 10.1016/j.jcrs.2009.06.037
|View full text |Cite
|
Sign up to set email alerts
|

Incision sizes at different stages of phacoemulsification with foldable intraocular lens implantation

Abstract: Incision enlargement occurred at different stages of phacoemulsification, mostly during IOL implantation. More than 72% of eyes had a final incision of 2.3 mm. Beginning with a 2.3 mm incision may prevent wound tears and surface irregularities.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
7
0
1

Year Published

2014
2014
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(10 citation statements)
references
References 41 publications
2
7
0
1
Order By: Relevance
“…In the present study, IOL insertion with D Monarch III and Unfolder Platinum cartridges widened the corneal incision by 0.13 mm in about 90% of patients with no significant differences emerging between devices. Our data concur with observations that, with diverse cartridge types, IOL implantation through a 2.2-mm clear corneal incision, was associated with incision enlargement in the majority of cases [6,14,15]. The ideal incision size was held to be 2.3 mm for the D cartridge with Monarch III with the wound assisted implantation technique, while 2.4 mm was believed to be the smallest incision the D cartridge tip could be fully inserted into [6,14,16].…”
Section: Discussionsupporting
confidence: 88%
See 1 more Smart Citation
“…In the present study, IOL insertion with D Monarch III and Unfolder Platinum cartridges widened the corneal incision by 0.13 mm in about 90% of patients with no significant differences emerging between devices. Our data concur with observations that, with diverse cartridge types, IOL implantation through a 2.2-mm clear corneal incision, was associated with incision enlargement in the majority of cases [6,14,15]. The ideal incision size was held to be 2.3 mm for the D cartridge with Monarch III with the wound assisted implantation technique, while 2.4 mm was believed to be the smallest incision the D cartridge tip could be fully inserted into [6,14,16].…”
Section: Discussionsupporting
confidence: 88%
“…Older studies reported that keratome type, IOL type and dioptric power might affect incision width, but cartridge insertion undoubtedly may contribute to its enlargement [10,11,12]. More recently, maximum incision stretch was observed to occur during IOL implantation [13,14].…”
Section: Discussionmentioning
confidence: 99%
“…10,11 Maximum incision stretch has been shown to occur during IOL implantation. 11 Steinert and Deacon 12 reported that an irreversible increase in incision size follows phacoemulsification surgery due to initial stretch-related incision tearing.…”
Section: Discussionmentioning
confidence: 99%
“…10,11 Maximum incision stretch has been shown to occur during IOL implantation. 11 Steinert and Deacon 12 reported that an irreversible increase in incision size follows phacoemulsification surgery due to initial stretch-related incision tearing. Various factors have been seen to affect the amount of incision enlargement, including dioptric power of IOL, 13 type of IOL, 14 type of keratome, 15 and speed of IOL insertion.…”
Section: Discussionmentioning
confidence: 99%
“…Some extent of incision enlargement and stretch pertain to intraocular surgery, especially when IOL injector systems are used [6,7,13,[15][16][17]. Wound enlargement can occur at various steps of cataract surgery, but mostly during lens insertion procedures [18]. In our study, incision size enlargement by IOL insertion was seen with all injector devices, and the degree of enlargement differed significantly among groups.…”
Section: Discussionmentioning
confidence: 45%